Thiamin, riboflavin, pyridoxine and niacin requirements of growing Japanese quail fed purified diets - Mak, T. K.; Vohra, Pran (Universiti Pertanian Malaysia, 1982)
Growing Japanese quail at 35 days of the experiment, weighed respectively, as follows when fed the various levels of a test vitamin in their diet: (a) thiamin hydrochloride (mg/kg diet), 1, 1.5, 2, 2.5, 3, and 3.5; body weight (g), 68.5, 94.8, 105.7, 103.3, 99.4 and 97.4. (b) riboflavin (mg/kg diet), 0.75, 1, 1.5, 2, 2.5, and 3; body weight (g), dead, 45.3, 72.6, 103.0, 100.2 and 103.9. (c) pyridoxine hydrochloride (mg/kg diet), 1, 1.5, 2, 2.5, 3, and 3.5; body weight (g), 91.9, 101.6, 102.5, 105.9, 105.7, and 103.2. (d) niacin (mg/kg diet), 5, 10,15, 20, 25, and 30; body weight (g), 93.8, 100.8, 105.2, 106.8, 101.9, and 109.4. The dietary supplements for growing Japanese quail are estimated to be as follows (mg/kg diet): thiamin hydrochloride, 1.5; riboflavin, 2; pyridoxine hydrochloride, 1.5; and niacin, 15.